A high-strength, high-toughness, high-conductivity graphene aluminum-based composite conductor for cable and preparation method thereof
By introducing graphene and other elements into aluminum-based composite materials and combining with specific preparation processes, the problem of easy breaking of single filaments of aluminum-based composite materials is solved, and the preparation of graphene aluminum-based composite materials with high strength, toughness and conductivity is achieved, improving the overall performance and service life of cable conductors.
Patent Information
- Application Number
- CN202410646334.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-23
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-05-23
Smart Images

Figure BDA0004854977970000091 
Figure BDA0004854977970000101
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of graphene aluminum-based composite materials, and in particular to a high-strength, high-toughness, high-conductivity graphene aluminum-based composite material conductor for cables and a preparation method thereof. Background Art
[0002] Aluminum-based composites have high specific strength and specific stiffness, good high temperature performance and wear resistance, and low thermal expansion coefficient. At present, the reinforcements of aluminum-based composites are mainly divided into particle reinforcements and fiber reinforcements. Fiber reinforcements not only improve the strength of the aluminum matrix, but also improve its plasticity. Carbon nanotubes are an important aluminum-based fiber reinforcement, but their production cost is high, and the potential for using carbon nanotubes to further enhance the performance of aluminum alloys is getting smaller and smaller.
[0003] Graphene is a new type of two-dimensional nanomaterial with a strength of up to 1.01TPa, which is 100 times that of structural steel, while its density is only 1 / 5 of that of structural steel. Compared with carbon nanotubes, it has greater specific strength, specific surface area and lower production cost, and is expected to replace carbon nanotubes as the most ideal filler and reinforcement in future composite materials. Therefore, using graphene to reinforce aluminum alloy is an important breakthrough to further improve aluminum-based composite materials, which is conducive to solving the shortcomings of the existing aluminum-based materials in the application of cable conductors, especially the shortcomings of the fifth and sixth conductors of soft structural conductors for cables. The existing aluminum alloy materials are very easy to break when they are made into 0.16-0.51mm single wires by small pulling (or micro-pulling), and this situation will also occur in the subsequent twisting and stamping of cable joints, leading to quality accidents.
[0004] Patent CN115466883A discloses a highly conductive graphene aluminum alloy rod, the alloy composition of which includes: graphene mass percentage of 0.10% to 0.30%, iron mass percentage of 0.05% to 0.14%, silicon mass percentage of 0.04% to 0.09%, copper mass percentage of 0.0001% to 0.01%, rare earth mass percentage of 0.02% to 0.04%, boron mass percentage of 0.01% to 0.02%, titanium, vanadium, manganese, chromium mass percentage of 0.00% to 0.02%, the mass percentage of other impurities is ≤0.03%, and the remainder is aluminum. The conductivity of the graphene aluminum alloy wire reaches 59.5% IACS, which is 1.71% higher than that of LHA3 aluminum alloy. This solution still has a lot of room for improving conductivity, and does not involve flexibility, impact toughness, creep and other aspects.
[0005] Patent CN107904459A discloses a method for preparing a graphene high-conductivity composite aluminum alloy for cables. The preparation method is simple and easy to master, and can effectively improve the reuse rate of recycled aluminum materials for cables. The production cost is low. On the one hand, it can effectively improve the guiding performance, corrosion resistance and high temperature resistance of aluminum-based conductors. On the other hand, it can effectively improve the structural strength, toughness, tensile strength, fatigue resistance and machining performance of aluminum-based conductors, thereby effectively providing the stability and reliability of the conductive performance of cable products, and also helping to reduce the production and preparation costs of cable products. However, the entire technical solution has not been tested, and the effects recorded cannot be judged and verified at all.
[0006] Patent CN 108060321 A discloses a method for preparing a graphene-enhanced aluminum-based composite material. In view of the uneven dispersion of graphene in an aluminum alloy matrix and the difficulty in combining with the matrix, a semi-solid extrusion casting method is adopted. The graphene-enhanced aluminum-based composite material is made by smelting in a smelting and stirring atmosphere furnace, electromagnetic stirring, pouring, and extrusion casting. This preparation method has advanced technology, accurate and detailed data, strict procedures, pure slurry, good metallographic structure density, and no shrinkage cavities or shrinkage. The prepared graphene-enhanced aluminum-based composite material has a hardness of 87H B, which is 69.92% higher than that of the matrix, a tensile strength of 255Mpa, which is 57.46% higher than that of the matrix, an elongation of 8%, which is 5% higher than that of the matrix, and a density of 99.6%. It is an advanced method for preparing graphene-enhanced aluminum-based composite materials.
[0007] The existing aluminum-based composite materials are very easy to break when they are made into 0.16-0.51mm single wires by small pulling (or micro pulling), and this situation will also occur in the subsequent twisting and stamping of cable joints, resulting in quality accidents. Graphene aluminum-based composite materials can be used in many occasions that require high cable flexibility, impact toughness, and high conductivity. Such as: a. Application of automotive wires, the flexibility of the wire is one of the important performance indicators for evaluating an automotive wire. In the design and manufacturing process of automotive wires, flexibility testing is an indispensable test item, which is directly related to the reliability and durability of automotive wires in use. In addition, good impact toughness is to ensure the quality of automotive wires when the terminal (connector) is impacted during installation. b. Application of charging pile wires, charging wires are one of the indispensable accessories for mobile devices, so the quality directly affects the service life and safety of mobile devices. If the swing strength of the charging wire is not enough, it is easy to wear or break, resulting in users being unable to charge normally or safety hazards. Therefore, it is very important to conduct a swing test on the charging wire. Passing the charging cable swing test helps to improve the quality and safety of the charging cable and reduce the problems and risks encountered by users during use.
[0008] Therefore, how to improve the performance of graphene aluminum-based composite conductors, especially toughness and high conductivity, remains the focus of research and also has significant economic value. Summary of the invention
[0009] Based on the needs and deficiencies of the prior art, the purpose of the present invention is to provide a high-strength, high-toughness, high-conductivity graphene aluminum-based composite conductor, and to apply it to the manufacture of cable conductors. The graphene aluminum-based composite material of the present invention is used to manufacture cable conductors with good high strength, good ductility, and high impact toughness. It is ensured that it is not easy to break during wire drawing and twisting, and the production efficiency is greatly improved. At the same time, it is ensured that the conductor is not easy to break during stamping of the installation terminal, and the conductivity is high (reducing the effective cross-section when replacing copper cables), the operation is stable, and the safe service life cycle is long.
[0010] The present invention solves the above technical problems by adopting the following technical solutions:
[0011] A high-strength, high-toughness, high-conductivity graphene aluminum-based composite conductor comprises the following components in weight percentage (%): 0.02-0.15 silicon, 0.2-1.0 iron, 0.1-0.40 copper, 0.01-0.08 vanadium, 0.01-0.08 graphene, 0.01-0.7 zirconium, 0.04-0.06 boron, 0.05-0.08 rare earth, the remainder is aluminum and impurities, a single impurity is less than 0.03, and the total is less than or equal to 0.10, wherein the maximum total content of iron and silicon is 1.1.
[0012] Furthermore, the rare earth is selected from one or more of lanthanum, cerium and scandium.
[0013] Furthermore, the high-strength, high-toughness, high-conductivity graphene aluminum-based composite conductor comprises the following components in weight percentage (%): silicon 0.05-0.10, iron 0.4-0.8, copper 0.2-0.30, vanadium 0.03-0.05, graphene 0.1-0.5, zirconium 0.04-0.06, boron 0.05-0.08, rare earth 0.2-0.3, and the remainder is aluminum and impurities, with a single impurity <0.03 and a total of ≤0.10, wherein the maximum total content of iron and silicon is 0.9.
[0014] Furthermore, the graphene aluminum-based composite material conductor contains a ZrB2 phase with a content of 0.001 to 0.002%; and contains a nano-Al3Zr dispersed phase with a content of 0.002 to 0.003%, wherein the nano-Al3Zr dispersed phase is distributed near the grain boundary.
[0015] Furthermore, the graphene aluminum-based composite conductor has a grain size of 47 to 56 μm, a tensile strength of 164 to 183 MPa, an elongation of 25.4 to 27.8%, a conductivity of 63.0 to 64.2% IACS, and an impact toughness of 22 to 25 J / cm 2 , creep amount is less than 0.2%.
[0016] A method for preparing a high-strength, high-toughness, and high-conductivity graphene aluminum-based composite conductor comprises the following steps:
[0017] (1) Melting:
[0018] According to the composition of the aluminum-based composite conductor, raw materials of corresponding composition are weighed, the aluminum raw materials are put into a crucible, heated to 730-750° C., the remaining raw materials are added and continuously stirred to form a uniform melt;
[0019] (2) Refining:
[0020] Keep the temperature at 730-750℃, add refining agent for refining in an inert protective atmosphere; after refining, perform slag removal operation;
[0021] (3) Degassing of holding furnace
[0022] In the heat preservation state, a mixed gas is introduced into the melt for degassing;
[0023] (4) Casting and continuous casting
[0024] The melt is cast and continuously cast to obtain an aluminum-based alloy rod, and the total cooling rate during the casting process is controlled to be 10-12°C / s;
[0025] (5) Tempering treatment
[0026] The aluminum-based alloy rod is placed in a toughening furnace for toughening at a temperature of 340 to 370°C and a toughening time of 4 to 5 hours;
[0027] (6) Wire drawing and aging treatment
[0028] The aluminum-based alloy rod after toughening treatment is subjected to wire drawing treatment and then put into an aging furnace for aging treatment;
[0029] (7) Bundle twisting and re-twisting
[0030] The aluminum-based alloy wire bundles are twisted and re-twisted to finally obtain the conductor for the cable.
[0031] Furthermore, in the refining process in step (2), permanent magnetic stirring is performed every 10 to 15 minutes, and each stirring time is 3 to 5 minutes.
[0032] Furthermore, in step (3), the mixed gas is 60-80 vol% Ar and 20-40 vol% Cl2.
[0033] Furthermore, in step (6), the wire drawing diameter is Φ0.16-0.51 mm, the aging treatment temperature is 160° C.-190° C., and the aging treatment time is 4-5 h.
[0034] Furthermore, in step (2), the inert protective atmosphere is Ar or N2.
[0035] This application prepares a graphene aluminum-based composite conductor with high strength, good ductility and high impact toughness by coordinating the element composition, content and preparation process. Specifically, aluminum is used as the matrix, and elements such as Si, Fe, Cu, V, GPE, Zr, B, and Re are added. After reasonable proportioning and limiting the maximum content between Fe and Si, the ideal performance of the various properties of the aluminum alloy material is guaranteed, so that the aluminum-based alloy material has good comprehensive performance and is suitable for the preparation of cable conductors, especially drawing. The single wire is easy to process into a soft conductor; it has high impact toughness, high conductivity and flexibility.
[0036] Specific:
[0037] Graphene (GPE) is reduced graphene, which is a layered material obtained by oxidizing graphite. Adding a certain amount of graphene to aluminum-based materials significantly changes the mechanical properties of the alloy material, improves the strength of the alloy metal, and makes the alloy metal have better toughness and bending properties; the weight percentage content of graphene is 0.01-0.7%; preferably, the content is 0.05-0.5%.
[0038] Vanadium (V) element, vanadium is usually added in trace amounts in aluminum alloys to form fine aluminum-vanadium intermetallic compound phases, which play a role in precipitation strengthening in the alloy, improving the creep resistance and toughness of the aluminum alloy; at the same time, V can also effectively improve the corrosion resistance of aluminum-based composite conductors. Therefore, the weight percentage content of rare earth elements is 0.03-0.05.
[0039] Rare earth (RE) elements, including scandium, cerium, lanthanum, or one or more, are excellent modifiers that improve the cast structure of the alloy, refine the grains, improve the structural properties of aluminum, and form stable nano-scale intermetallic compounds with certain elements in the alloy that precipitate from the crystals. These precipitated phases can form grain boundaries. Therefore, the weight percentage of rare earth elements is 0.02-0.5%.
[0040] Zirconium (Zr) element plays the role of nucleating agent in aluminum melt and can promote heterogeneous nucleation during casting, so as to achieve the effect of grain refinement and reduce dendrite segregation. On the other hand, Zr element can partially form nano ZrB2 reinforcement phase with B element, which can significantly improve the mechanical properties of aluminum-based materials. At the same time, a part of Zr element forms nano Al3Zr dispersion phase with aluminum matrix and distributes near grain boundary. The synergistic cooperation between Zr, B and Al elements significantly improves the impact toughness of graphene aluminum-based composite materials. However, the addition of Zr element will reduce the conductivity to a certain extent; therefore, the weight percentage content of zirconium (Zr) element is 0.04-0.06%.
[0041] Boron (B) element, on the one hand, can also play a role in refining grains in aluminum alloys, improve the strength and elongation of the alloy, and make the alloy have better fatigue resistance; at the same time, boron element and zirconium element form the above-mentioned nano ZrB2 reinforcement phase. Therefore, the weight percentage content of boron (B) element is 0.05-0.08%.
[0042] Furthermore, during the casting process, graphene is prone to agglomeration between carbon molecular layers, which is not conducive to dispersion. In order to ensure uniform distribution of the components of the entire furnace of aluminum alloy liquid, it must be stirred every 20 minutes during the refining of the aluminum alloy solution. Permanent magnetic stirring is used, and each stirring is to the corners of the furnace, and the stirring time is 5 to 7 minutes. Because graphene has a special single-layer honeycomb structure, it has good mechanical properties. The connection between carbon atoms is in a very flexible state. When mechanical force is applied externally, the carbon atom surface will bend and deform, and the structure remains stable. In addition, it has very high electrical properties, and its conductivity is much higher than any current high-temperature superconducting material. Only by ensuring the full uniformity of the graphene component in the aluminum-based composite material solution can the cast graphene aluminum-based composite material have good toughness and extremely high conductivity. In addition, the cooling rate can be appropriately selected during the casting process, preferably 10 to 12 ° C / second, to achieve rapid solidification at the cooling rate, thereby obtaining an ingot with a finer structure.
[0043] Furthermore, in order to better exert the flexibility of the twisted conductor, when using the graphene aluminum-based composite material to process the conductor, special emphasis is placed on filling high-elasticity and high-temperature resistant fibers when twisting and re-twisting the single-filament bundles, squeezing the gaps, and ensuring comprehensive and uniform stress when the cable conductor is squeezed by external force. The twisted single wires require aging treatment, and the aging furnace treatment temperature is preferably 160℃~190℃ according to the single wire diameter (Ф0.16~0.51mm), and the insulation time is 4~5h. The twisted conductor meets the requirements such as the flexibility of the automotive line pair and the impact toughness when installing the terminal (connector); as a charging pile cable conductor, it needs to pass the swing test requirements, etc.
[0044] Compared with the prior art, the present invention has the following beneficial effects:
[0045] (1) The prepared conductor has good high strength, good ductility, and high impact toughness, and can effectively solve the defect of short service life of charging cables. It is helpful to solve the disadvantages of the application of existing aluminum-based composite materials in cable conductors, especially the disadvantages of the fifth and sixth conductors of soft structures for cables; it can be widely used in new energy vehicle charging cables and has great economic value.
[0046] (2) The conductor can also be used in other fields and has strong scalability.
[0047] (3) The conductor preparation process of the present invention is simple, low-cost and highly competitive. DETAILED DESCRIPTION
[0048] The embodiments of the present invention will be described in detail below with reference to examples, but those skilled in the art will understand that the following examples are only used to illustrate the present invention and should not be construed as limiting the scope of the present invention.
[0049] Example 1
[0050] A high-strength, high-toughness, high-conductivity graphene aluminum-based composite conductor comprises the following components in weight percentage (%): 0.02 silicon, 0.4 iron, 0.1 copper, 0.02 vanadium, 0.01 graphene, 0.04 zirconium, 0.05 boron, 0.01 lanthanum, 0.01 cerium, and the balance is aluminum and impurities.
[0051] The method for preparing the above-mentioned high-toughness, high-conductivity graphene aluminum-based composite conductor comprises the following steps:
[0052] (1) Melting:
[0053] According to the composition of the aluminum-based composite conductor, raw materials of corresponding composition are weighed, the aluminum raw materials are put into a crucible, heated to 730° C., the remaining raw materials are added and continuously stirred to form a uniform melt;
[0054] (2) Refining:
[0055] Keep the temperature at 730℃, add refining agent and carry out refining in an inert protective atmosphere of Ar; after the refining is completed, carry out slag removal operation;
[0056] (3) Degassing of holding furnace
[0057] In the heat preservation state, a mixed gas is introduced into the melt for degassing;
[0058] (4) Casting and continuous casting
[0059] The melt is cast and continuously cast to obtain an aluminum-based alloy rod, and the total cooling rate during the casting process is controlled to be 10°C / s;
[0060] (5) Tempering treatment
[0061] The aluminum-based alloy rod is placed in a toughening furnace for toughening at a temperature of 340°C and a toughening time of 4 hours;
[0062] (6) Wire drawing and aging treatment
[0063] The aluminum-based alloy rod after toughening treatment is subjected to wire drawing treatment and then put into an aging furnace for aging treatment;
[0064] (7) Bundle twisting and re-twisting
[0065] The aluminum-based alloy wire bundles are twisted and re-twisted to finally obtain the conductor for the cable.
[0066] Wherein, in the refining process in step (2), permanent magnetic stirring is performed every 10 minutes, and each stirring time is 3 minutes.
[0067] Wherein, the mixed gas in step (3) is 60 vol% Ar and 40 vol% Cl2.
[0068] Wherein, in step (6), the wire drawing diameter is Ф0.2 mm, the aging treatment temperature is 165° C., and the aging treatment time is 4 h.
[0069] Example 2
[0070] A high-strength, high-toughness, high-conductivity graphene aluminum-based composite conductor comprises the following components in weight percentage (%): 0.14 silicon, 0.9 iron, 0.4 copper, 0.08 vanadium, 0.7 graphene, 0.06 zirconium, 0.08 boron, 0.02 lanthanum, 0.01 scandium, and the balance is aluminum and impurities.
[0071] The method for preparing the above-mentioned high-toughness, high-conductivity graphene aluminum-based composite conductor comprises the following steps:
[0072] (1) Melting:
[0073] According to the composition of the aluminum-based composite conductor, raw materials of corresponding composition are weighed, the aluminum raw materials are put into a crucible, heated to 750° C., the remaining raw materials are added and continuously stirred to form a uniform melt;
[0074] (2) Refining:
[0075] Maintain the temperature at 750°C, add refining agent and carry out refining in an inert protective atmosphere of Ar; after the refining is completed, carry out slag removal operation;
[0076] (3) Degassing of holding furnace
[0077] In the heat preservation state, a mixed gas is introduced into the melt for degassing;
[0078] (4) Casting and continuous casting
[0079] The melt is cast and continuously cast to obtain aluminum-based alloy rods, and the total cooling rate during the casting process is controlled to be 12°C / s;
[0080] (5) Tempering treatment
[0081] The aluminum-based alloy rod is placed in a toughening furnace for toughening at a temperature of 370°C and a toughening time of 5 hours;
[0082] (6) Wire drawing and aging treatment
[0083] The aluminum-based alloy rod after toughening treatment is subjected to wire drawing treatment and then put into an aging furnace for aging treatment;
[0084] (7) Bundle twisting and re-twisting
[0085] The aluminum-based alloy wire bundles are twisted and re-twisted to finally obtain the conductor for the cable.
[0086] Wherein, in the refining process in step (2), permanent magnetic stirring is performed every 15 minutes, and each stirring time is 5 minutes.
[0087] Wherein, the mixed gas in step (3) is 80 vol% Ar and 20 vol% Cl2.
[0088] Wherein, in step (6), the wire drawing diameter is Ф0.5 mm, the aging treatment temperature is 190° C., and the aging treatment time is 5 h.
[0089] Example 3
[0090] A high-strength, high-toughness, high-conductivity graphene aluminum-based composite conductor comprises the following components in weight percentage (%): 0.04 silicon, 0.5 iron, 0.2 copper, 0.03 vanadium, 0.1 graphene, 0.04 zirconium, 0.05 boron, 0.1 cerium, 0.1 scandium, and the balance is aluminum and impurities.
[0091] The method for preparing the above-mentioned high-toughness, high-conductivity graphene aluminum-based composite conductor comprises the following steps:
[0092] (1) Melting:
[0093] According to the composition of the aluminum-based composite conductor, raw materials of corresponding composition are weighed, the aluminum raw materials are put into a crucible, heated to 740° C., the remaining raw materials are added and continuously stirred to form a uniform melt;
[0094] (2) Refining:
[0095] Keep the temperature at 740℃, add refining agent and carry out refining in an inert protective atmosphere of Ar; after the refining is completed, carry out slag removal operation;
[0096] (3) Degassing of holding furnace
[0097] In the heat preservation state, a mixed gas is introduced into the melt for degassing;
[0098] (4) Casting and continuous casting
[0099] The melt is cast and continuously cast to obtain aluminum-based alloy rods, and the total cooling rate during the casting process is controlled to be 11°C / s;
[0100] (5) Tempering treatment
[0101] The aluminum-based alloy rod is placed in a toughening furnace for toughening at a temperature of 350°C and a toughening time of 4.5 hours;
[0102] (6) Wire drawing and aging treatment
[0103] The aluminum-based alloy rod after toughening treatment is subjected to wire drawing treatment and then put into an aging furnace for aging treatment;
[0104] (7) Bundle twisting and re-twisting
[0105] The aluminum-based alloy wire bundles are twisted and re-twisted to finally obtain the conductor for the cable.
[0106] Wherein, in the refining process in step (2), permanent magnetic stirring is performed every 15 minutes, and each stirring time is 4 minutes.
[0107] Wherein, the mixed gas in step (3) is 70 vol% Ar and 30 vol% Cl2.
[0108] Wherein, in step (6), the wire drawing diameter is Ф0.3 mm, the aging treatment temperature is 175° C., and the aging treatment time is 4.2 h.
[0109] Example 4
[0110] A high-strength, high-toughness, high-conductivity graphene aluminum-based composite conductor comprises the following components in weight percentage (%): 0.1 silicon, 0.8 iron, 0.3 copper, 0.05 vanadium, 0.5 graphene, 0.06 zirconium, 0.07 boron, 0.1 lanthanum, 0.1 cerium, 0.1 scandium, and the balance is aluminum and impurities.
[0111] The method for preparing the above-mentioned high-toughness, high-conductivity graphene aluminum-based composite conductor comprises the following steps:
[0112] (1) Melting:
[0113] According to the composition of the aluminum-based composite conductor, raw materials of corresponding composition are weighed, the aluminum raw materials are put into a crucible, heated to 745° C., the remaining raw materials are added and continuously stirred to form a uniform melt;
[0114] (2) Refining:
[0115] Keep the temperature at 745℃, add refining agent and carry out refining in an inert protective atmosphere of Ar; after the refining is completed, carry out slag removal operation;
[0116] (3) Degassing of holding furnace
[0117] In the heat preservation state, a mixed gas is introduced into the melt for degassing;
[0118] (4) Casting and continuous casting
[0119] The melt is cast and continuously cast to obtain aluminum-based alloy rods, and the total cooling rate during the casting process is controlled to be 11°C / s;
[0120] (5) Tempering treatment
[0121] The aluminum-based alloy rod is placed in a toughening furnace for toughening at a temperature of 360°C and a toughening time of 4.5 hours;
[0122] (6) Wire drawing and aging treatment
[0123] The aluminum-based alloy rod after toughening treatment is subjected to wire drawing treatment and then put into an aging furnace for aging treatment;
[0124] (7) Bundle twisting and re-twisting
[0125] The aluminum-based alloy wire bundles are twisted and re-twisted to finally obtain the conductor for the cable.
[0126] Wherein, in the refining process in step (2), permanent magnetic stirring is performed every 15 minutes, and each stirring time is 4 minutes.
[0127] Wherein, the mixed gas in step (3) is 70 vol% Ar and 30 vol% Cl2.
[0128] Wherein, in step (6), the wire drawing diameter is Ф0.4 mm, the aging treatment temperature is 180° C., and the aging treatment time is 4.6 h.
[0129] In order to better consider the influence of element composition and process on the performance of graphene aluminum-based composite conductor, Example 4 is used as a reference and a single factor change is performed to determine it.
[0130] Comparative Example 1
[0131] Comparative Example 1 is substantially the same as Example 4, except that Comparative Example 1 does not contain vanadium (V) element.
[0132] Comparative Example 2
[0133] Comparative Example 2 is substantially the same as Example 4, except that Comparative Example 2 does not contain zirconium (Zr) element.
[0134] Comparative Example 3
[0135] Comparative Example 3 is substantially the same as Example 4, except that the zirconium (Zr) element content in Comparative Example 3 is 0.1%.
[0136] Comparative Example 4
[0137] Comparative Example 4 is substantially the same as Example 4, except that the aging treatment temperature in Comparative Example 4 is 220°C.
[0138] The performance of the graphene aluminum-based composite conductors prepared in the above Examples 1 to 4 and Comparative Examples 1 to 4 was tested.
[0139] Specifically, the tensile strength and elongation tests can be conducted according to the "Bare Wire Test Method Part 3 Tensile Test", the conductivity test is conducted according to the "Wire and Cable Electrical Performance Test Method Part 2 Metallic Material Resistivity Test", the impact toughness test is conducted according to the "Metallic Material Charpy Impact Test EN10045", and the creep test is conducted according to the "Aluminum Alloy Wire for Cable Conductors GB / T30552 Appendix B", and the test conditions are: creep temperature of 200°C, stress of 60MPa, 100h. The grain size can be obtained by scanning electron microscopy of the conductor cross section; the conductor cross section is tested using an X-ray diffractometer, and the content of the ZrB2 phase and nano-Al3Zr dispersed phase can be calculated from the diffraction peak intensity corresponding to the XRD spectrum.
[0140] The specific test and calculation data are recorded in Tables 1-2.
[0141] Table 1
[0142]
[0143] It can be seen from the above data that in Example 4 and Comparative Example 1, the addition of V element has no significant effect on the internal structure of the graphene aluminum-based composite conductor. Without adding Zr raw material, no ZrB2 phase or nano-Al3Zr dispersed phase was detected in the obtained graphene aluminum-based composite conductor. Since the Zr element content in Comparative Example 3 is 0.1%, which is significantly higher than 0.06% in Example 4, the detected ZrB2 phase and nano-Al3Zr dispersed phase also increase accordingly, which is in line with the general basic principles of chemistry. Compared with Comparative Example 4, the content of ZrB2 phase and nano-Al3Zr dispersed phase is increased compared with Example 4, and the grain size is also significantly larger; this is because the higher the aging temperature, the more conducive to the generation of ZrB2 phase and nano-Al3Zr dispersed phase, but the effect on grain size is very unfavorable.
[0144] Table 2
[0145]
[0146] It can be seen from the data of Examples 1 to 4 that the graphene aluminum-based composite material conductor prepared by the present invention has good high strength, good elongation, and high impact toughness; the creep amount is less than 0.2% for 100 hours under the conditions of 200°C and 60MPa, and it has excellent heat resistance and can be effectively used in high temperature environments; it can effectively ensure that it is not easy to break during wire drawing and twisting, and the production efficiency is greatly improved. At the same time, it can ensure that the conductor is not easy to break when the terminal is stamped, the conductivity is high, the operation is stable, and the safe service life cycle is long.
[0147] The various properties of comparative example 1 are basically the same as those of example 4, indicating that the addition of element V has no significant effect on various properties.
[0148] Comparative Example 2 does not contain zirconium (Zr), but data comparison shows that the changes in tensile strength and elongation are not obvious. However, the addition of zirconium has a certain adverse effect on conductivity; however, the impact toughness is significantly reduced from 24.8 to 17.3 J / cm 2 . It can be seen that the addition of zirconium element to the graphene aluminum-based composite conductor is very beneficial. Although the addition of zirconium element is very beneficial, as the Zr element content increases, the impact toughness of the material also tends to increase (Comparative Example 3); however, a higher content will also lead to a significant decrease in conductivity, from 63.9% IACS to 57.6% IACS. Therefore, based on the balance between conductivity and impact toughness, the present invention controls zirconium 0.04-0.06 and boron 0.05-0.08. The data of Comparative Example 4 shows a significant change in impact toughness, which shows that the higher the aging treatment temperature is, the more unfavorable the effect on impact toughness.
[0149] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A high-strength, high-toughness, high-conductivity graphene aluminum-based composite conductor, characterized in that: The invention comprises the following components in weight percentage: silicon 0.02-0.15, iron 0.2-1.0, copper 0.1-0.40, vanadium 0.01-0.08, graphene 0.01-0.7, zirconium 0.04-0.06, boron 0.05-0.08, rare earth 0.02-0.5, and the balance is aluminum and impurities, with a single impurity less than 0.03 and a total of ≤0.10, wherein the maximum total content of iron and silicon is 1.1; The rare earth is selected from one or more of lanthanum, cerium and scandium; The graphene aluminum-based composite conductor contains a ZrB2 phase with a content of 0.001 to 0.002 wt.%; and contains a nano-Al3Zr dispersed phase with a content of 0.002 to 0.003 wt.%, wherein the nano-Al3Zr dispersed phase is distributed near the grain boundary; The grain size of the graphene aluminum-based composite conductor is 47-56 μm, the tensile strength is 164-183 MPa, the elongation is 25.4-27.8%, the conductivity is 63.0-64.2% IACS, and the impact toughness is 22-25 J / cm 2 , creep amount is less than 0.2%; The method for preparing the high-strength, high-toughness, and high-conductivity graphene aluminum-based composite conductor comprises the following steps: (1) Melting: According to the composition of the aluminum-based composite conductor, raw materials of corresponding composition are weighed, the aluminum raw materials are put into a crucible, heated to 730-750° C., the remaining raw materials are added and continuously stirred to form a uniform melt; (2) Refining: Keep the temperature at 730-750℃, add refining agent for refining in an inert protective atmosphere; after refining, perform slag removal operation; (3) Degassing of holding furnace In the heat preservation state, a mixed gas is introduced into the melt for degassing; (4) Continuous casting The melt is continuously cast to obtain an aluminum-based alloy rod, and the cooling rate is controlled to be 10-12°C / s during the continuous casting process; (5) Tempering treatment The aluminum-based alloy rod is placed in a toughening furnace for toughening at a temperature of 340 to 370°C and a toughening time of 4 to 5 hours; (6) Wire drawing and aging treatment The aluminum-based alloy rod after toughening treatment is subjected to wire drawing treatment and then put into an aging furnace for aging treatment; (7) Bundle twisting and re-twisting The aluminum-based alloy wire bundles are twisted and re-twisted to finally obtain a conductor for a cable; In step (3), the mixed gas is 60-80 vol% Ar and 20-40 vol% Cl2; In step (6), the wire drawing diameter is 0.16-0.51 mm, the aging treatment temperature is 160° C.-190° C., and the aging treatment time is 4-5 h.
2. The high-strength, high-toughness, high-conductivity graphene aluminum-based composite conductor according to claim 1, characterized in that: The invention comprises the following components in weight percentage: silicon 0.05-0.10, iron 0.4-0.8, copper 0.2-0.30, vanadium 0.03-0.05, graphene 0.1-0.5, zirconium 0.04-0.06, boron 0.05-0.08, rare earth 0.2-0.3, and the remainder is aluminum and impurities, wherein a single impurity is less than 0.03 and the total is less than or equal to 0.10, wherein the maximum total content of iron and silicon is 0.
9.
3. The high-strength, high-toughness, high-conductivity graphene aluminum-based composite conductor according to any one of claims 1 to 2, characterized in that: In the refining process in step (2), permanent magnetic stirring is performed every 10 to 15 minutes, and each stirring time is 3 to 5 minutes.
Citation Information
Patent Citations
High-conductivity graphene composite aluminum alloy for cable and preparation method thereof
CN107904459A
Preparation method of graphene-reinforced aluminum matrix composite
CN108060321A
High-conductivity heat-resistant aluminium alloy containing alkaline-earth metals
CN103952601A
High-conductivity graphene aluminum alloy rod, preparation method thereof and high-conductivity graphene aluminum alloy stranded wire
CN115466883A
Cited By
High-strength aluminum conductor cable
CN122224575A